A design exercise inspired by Pina Bausch. - Li, Wenjin. (2012)
In this year long design exercise, I attempted to translate modern dance aesthetic into a formal language and applied it to chair designs. Through this practice, I wish to address the question of whether aesthetical values are transferable.